BIOMINERALOGICAL STUDIES OF BLACK SEA FORAMINIFERA AS INDICATORS OF ENVIRONMENTAL CHANGES - Kravchuk, Anna (Sworld-Us Conference proceedings, 2025)
The paper considers the application of biomineralogical studies of benthic foraminifera to assess the geoecological situation on the Black Sea shelf. X-ray diffraction characteristics of the mineral composition of shells with morphological disorders and